2006
DOI: 10.1080/01485010600692017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Bmi, Total Testosterone, Sex Hormone-Binding-Globulin, Leptin, Insulin and Insulin Resistance in Obese Men

Abstract: The objective of this work was to evaluate the relationship between sex steroid hormones, sex hormone-binding-globulin, leptin, insulin and insulin resistance in obese men. Anthropometrical indexes, total testosterone (Tt), free testosterone (fT), estradiol (E), sex hormone-binding-globulin (SHBG), glucemia, insulin and leptin were measured in 77 men, with ages between 20 and 60 years. According to their body mass index (BMI), subjects were grouped into three categories: normal body weight (< 24.9 kg/m2), over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
89
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(104 citation statements)
references
References 38 publications
11
89
1
3
Order By: Relevance
“…Consistent with this notion, androgen deficiency has been associated with insulin resistance, type 2 diabetes mellitus, metabolic syndrome, and increased deposition of visceral fat. [62][63][64][65] In the TIMES2 (Testosterone Replacement In Hypogonadal Men With Either Metabolic Syndrome or Type 2 Diabetes) study, 6 to 12 months of transdermal TRT (vs placebo) significantly improved insulin resistance and glycemic control in a large randomized study of hypogonadal men with type 2 diabetes mellitus (ACCF/AHA class Ib). 66 A meta-analysis of 5 other randomized controlled trials (including 3 placebo-controlled trials) with mean follow-up of 58 weeks found that TRT was associated with a significant reduction in fasting plasma glucose levels, homeostasis model assessment of insulin resistance index, triglycerides, and WC.…”
Section: Recommended Assessments and Risk Clarificationmentioning
confidence: 99%
“…Consistent with this notion, androgen deficiency has been associated with insulin resistance, type 2 diabetes mellitus, metabolic syndrome, and increased deposition of visceral fat. [62][63][64][65] In the TIMES2 (Testosterone Replacement In Hypogonadal Men With Either Metabolic Syndrome or Type 2 Diabetes) study, 6 to 12 months of transdermal TRT (vs placebo) significantly improved insulin resistance and glycemic control in a large randomized study of hypogonadal men with type 2 diabetes mellitus (ACCF/AHA class Ib). 66 A meta-analysis of 5 other randomized controlled trials (including 3 placebo-controlled trials) with mean follow-up of 58 weeks found that TRT was associated with a significant reduction in fasting plasma glucose levels, homeostasis model assessment of insulin resistance index, triglycerides, and WC.…”
Section: Recommended Assessments and Risk Clarificationmentioning
confidence: 99%
“…Similarly, Haffner et al demonstrated that low sex hormone-binding globulin (SHBG) and testosterone levels are associated with higher glucose and insulin levels and increased obesity (8). Osuna et al correlated waist circumference, body mass index (BMI), insulin, and homeostatic model assessment of insulin resistance (HOMA-IR) to testosterone levels and, in each case, found a significant negative correlation with all these parameters (10). These findings when taken together, raise the possibility that testosterone may be having a protective function against the development of diabetes mellitus in men.…”
Section: Introductionmentioning
confidence: 99%
“…There is a close association between insulin resistance (IR) and testosterone deficiency 27. Free and total testosterone levels are inversely correlated with indices of IR such as insulin levels and homeostatic model assessment of insulin resistance (HOMA‐IR) 28, 29, 30. In this case report, the patient's suboptimal testosterone replacement may have further contributed to poor glycemic control 31 and cardiac performance 32.…”
Section: Discussionmentioning
confidence: 83%